Interactions And Contributions Between Islamic Human Development Index , Economic Growth, Fiscal Policy And Demographics In Indonesian Provinces : Panel Vector Autoregression (P-Var) Analisys - Rukiah Rukiah; Saparuddin Siregar (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to analyze the interactions and contributions between the Islamic Human Development Index (IHDI), economic growth, fiscal policy, and demographics in Indonesia's provinces. The method of analysis uses the Vector Autoregression Panel (PVAR) with a Sample of 33 Provinces in Indonesia. The findings in this study state that long-term estimates of Economic Growth have a positive and insignificant effect on IHDI in Indonesia, health and education Fiscal policies and demographics have a positive and significant effect on IHDI Provinces in Indonesia. The conclusion of this study states that IHDI is a variable that is strongly influenced by fiscal policy, demographic conditions and also policies in achieving economic growth in each province. The existence of the IHDI gap in each province shows that there is an imbalance of development and loss of moral and spiritual foundation in every development achievement.